Investigation of the optical and radiation shielding parameters of erbium-doped zinc sodium tungsten borate glass using MCNP5 simulations - Usman Iliyasu; Mohamad Syazwan Mohd Sanusi; Nor Ezzaty Ahmad (Materials Research Express)
This study explores the potential of (20Na _2 O+25ZnO+10WO _3 +(60-x)B _2 O _3 +xEr _2 O _3 where x = 0.1, 0.5, 0.7, and 1 mol%) glass for optical and radiation shielding applications, fabricated using the melt quenching method. Optical, structural, and radiation shielding properties were analyzed using UV–visible spectroscopy, XRD, FTIR, MCNP5, and Phy-X/PSD software. Results show a 9.01% decrease in refractive index from 2.22 to 2.02 and a significant increase in band gap energy from 2.29 eV to 3.12 eV with increasing Er _2 O _3 content. The addition of Er ^3+ ions convert BO _3 units into BO _4 units, creating a denser glass network. The linear attenuation coefficient ( ${LAC}$ ) increased in BTEr1 glass to 0.676 cm ^−1 , compared to 0.607 cm ^−1 for BTEr0.1 glass, reflecting an approximate rise of 11.5% in ${LAC}.$ The BTEr1 glass shows enhanced radiation shielding, with a 10.25% reduction in the half-value layer (HVL) from 1.15 cm in BTEr0.1 to 1.03 cm in BTEr1 at 0.284 MeV, and a further reduction of 8.17% from 4.77 cm in BTEr0.1 to 4.42 cm in BTEr1 at 2.506 MeV for 0.1 and 1 mol% Er _2 O _3 level in the BTEr glass. The BTEr glass enhances light transmission in the visible spectrum and increases glass stability with Er _2 O _3 addition , making it suitable for advanced optical applications. Additionally, its improved photon radiation shielding properties make it a promising candidate for radiation protection.